2018
DOI: 10.26434/chemrxiv.7319273.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ammonia as Proton Conducting Medium Confined in Porous Materials

Abstract: <b></b><p>Molecular confinement within a limited space induces unique behaviour not seen in bulk systems. In particular, the proton diffusion in conducting medium under confined conditions is significantly affected by the surrounding environment.H<sub>2</sub>O, efficient conducting medium, confined in hydrophobic channels forms unique clusters allowing rapid diffusion, whereas confined NH<sub>3</sub>, having a similar degenerate system (Fig. 1a), has not been reported.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…21). 76 As mentioned above, pure NH 3 molecules are converted to NH 4 + by protonation from the dangling –(COOH) 2 in the ligand. Furthermore, one of the NH 3 molecules has an interaction with the μ 2 -OH bridge.…”
Section: Ammonia-based Degenerate System For Proton Conduction In Mofsmentioning
confidence: 98%
See 1 more Smart Citation
“…21). 76 As mentioned above, pure NH 3 molecules are converted to NH 4 + by protonation from the dangling –(COOH) 2 in the ligand. Furthermore, one of the NH 3 molecules has an interaction with the μ 2 -OH bridge.…”
Section: Ammonia-based Degenerate System For Proton Conduction In Mofsmentioning
confidence: 98%
“…Previous studies have demonstrated NH 3 (NH 4 + )-mediated proton conductors through the simultaneous introduction of the NH 4 + counterion during MOF synthesis or aqueous-NH 3 vapor loading exhibiting an improved proton conductivity. Anhydrous NH 3 -mediated proton conductivity was reported recently using MIL-53(Al) derivative MOFs through pure NH 3 gas adsorption 76. MIL-53 (Al) derivatives that are well known for their high stability are synthesized from Al III ions and H 2 bdc ligands with various functional groups, (H 2 bdc–(COOH) 2 , 1 ), (H 2 bdc–(NH 2 ), 2 ), (H 2 bdc–(OH), 3 ), and (H 2 bdc, 4 ), indicating the difference in proton-donating ability (p K a ).…”
Section: Ammonia-based Degenerate System For Proton Conduction In Mofsmentioning
confidence: 99%